ANALISA STRATEGI MARKETING MIX MENGGUNAKAN KONSEP 4P (PRODUCT, PLACE, PRICE, PROMOTION)) PADA PT ARMSTRONG INDUSTRI HALUAN INDONESIA - Farah Putri Sanhar; Dana Prianjani (Jurnal Industri dan Teknologi Samawa, 2023)
This study aims to analyze how the marketing mix strategy at PT. Amstrong Indonesian Bow Industry uses the 4P concept (Product, Place, Price Promotion). PT Armstrong Industri Indonesia is a company engaged in the manufacturing of rubber, sponge, plastic and other adhesive components. Methods of data collection include field studies, observations and interviews and literature studies are carried out by researching literature that is relevant to the object of observation. The results of the analysis obtained are product, price, place, promotion variables that have a significant simultaneous effect on customer satisfaction at PT Arsmstrong Industri Indonesia. Based on the results of the regression test for the product, price, place, promotion variables, it can be seen that the value 34.757 is greater than the value 2.53 at the Sig. ANOVA 0.000 is less than 0.05. These results were obtained from data processing using SPSS software.